2005
DOI: 10.1021/jp052970k
|View full text |Cite
|
Sign up to set email alerts
|

Potential Energy Surfaces, Product Distributions and Thermal Rate Coefficients of the Reaction of O(3P) with C2H4(XAg):  A Comprehensive Theoretical Study

Abstract: The potential energy surface for the O((3)P) + C(2)H(4) reaction, which plays an important role in C(2)H(4)/O(2) flames and in hydrocarbon combustion in general, was theoretically reinvestigated using various quantum chemical methods, including G3, CBS-QB3, G2M(CC,MP2), and MRCI. The energy surfaces of both the lowest-lying triplet and singlet electronic states were constructed. The primary product distribution for the multiwell multichannel reaction was then determined by RRKM statistical rate theory and weak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
156
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(178 citation statements)
references
References 62 publications
18
156
4
Order By: Relevance
“…A third channel producing CH 2 CO (ketene) + H 2 was ascribed a 5% weighting. A recent theoretical study from Nguyen et al [23] produced a total rate constant similar to Baulch et al's recommendation but with different product ratios. The theoretical study predicts the same major products as Baulch et al, but the formation of formaldehyde and triplet methylene also becomes an important product set as the temperature increases.…”
Section: B C2h4+ Ch2ch + / ċH3+hċomentioning
confidence: 68%
See 1 more Smart Citation
“…A third channel producing CH 2 CO (ketene) + H 2 was ascribed a 5% weighting. A recent theoretical study from Nguyen et al [23] produced a total rate constant similar to Baulch et al's recommendation but with different product ratios. The theoretical study predicts the same major products as Baulch et al, but the formation of formaldehyde and triplet methylene also becomes an important product set as the temperature increases.…”
Section: B C2h4+ Ch2ch + / ċH3+hċomentioning
confidence: 68%
“…While further improvement is still needed, the current version is much improved over the original one as a result of the experiments and modeling presented in Kopp et al [1] and the present paper, respectively. ... [2] ... [9] ... [4] ... [13] ... [11] ... [12] ... [16] ... [8] ... [17] ... [7] ... [14] ... [10] ... [15] ... [19] ... [5] ... [20] ... [6] ... [21] ... [1] ... [22] ... [18] ... [23] Ċ ... [34] ... [31] ... [35] ... [32] ... [36] ... [33] ... [30] ... [37] ... [26] ... [38] ... [27] ... [39] ... [28] ... [40] ... [24] ... [41] ... [25] ... [42] …”
Section: Discussionmentioning
confidence: 99%
“…Reaction (11) is also a major product found in the theoretical study 31 based on various quantum chemical methods. Peeters and Maes 32 have measured this reaction.…”
Section: Resultsmentioning
confidence: 97%
“…C 2 H 4 , and then by the O( 3 P) þ C 2 H 4 reaction. This molecule has been theoretically investigated 31 using various quantum chemical methods, and it was found that one of its major products is through the reaction channel…”
Section: Resultsmentioning
confidence: 99%
“…This is one of the major possible primary product channels with experimental reaction enthalpy (D r H(0K)) of 223 and 229 kJ/mol obtained by quantum chemical calculations. 22 • Population of HCO The HCO specie can be produced by different channels, such as R5. It has experimental D r H of 2117 kJ/mol, whereas by quantum chemical calculations the value is 2121 kJ/mol.…”
mentioning
confidence: 99%